Marketing Strategies of Wawasan Newspaper in Maintaining Market Share in Semarang - Septiawan, Hendras; Rusdarti, Rusdarti; Haryati, Titik (Journal of Economic Education, 2020)
This research aims to determine the internal and external conditions of Wawasan Newspaper based on SWOT analysis in maintaining market share in Semarang. This uses descriptive research type with quantitative approach through three stages of strategy formulation, namely: the input stage, the matching stage, and the decision-making stage. In the first stage, IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation) matrices are used. In the second stage, the IE Matrix (internal-External) and the SWOT Matrix (Strengths, Weaknesses, Opportunities, and Threats) are used. In stage three, QSPM (Quantitative Strategic Planning Matrix) is used. The results of this study are: In the first stage, the results of the IFE (Internal Factor Evaluation) matrix obtained a weighted score of 2.356, while the results of the EFE (External Factor Evaluation) matrix resulted in a weighted score of 2.18. In the matching stage, IE (Internal-External) Matrix of the company is in a stable position. Marketing strategies that are feasible to use are market penetration and product development. In the decision-making stage, an alternative strategy that can be implemented in Wawasan Newspaper namely market penetration with a TAS of 4.406 is obtained.